Matemática financeira: o estudo de empréstimos consignados e consórcios voltados para o ensino médio - Paula Neto, Antônio Sabino de (2014)
We live in a world with many computational resources, financial spreadsheets or graphical calculators. Become indisputable and indispensable addition to these features we need at least the basic concepts of financial mathematics to a more accurate understanding of the subject, enabling the application of financial calculations in making decisions. The objective of this dissertation is to show how it behaves payroll loans and consortia seeking to make direct connection with our reality.